Pengaruh Tekanan Anggaran Waktu terhadap Kualitas Audit Dimediasi Kemahiran Profesional - Kholifahtul, Indartik; Sari, Rida Perwita (Universitas Pendidikan Ganesha, 2021)
This study aims to examine due professional care in mediating the effect of time budget pressure on audit quality. The sampling method used was convenience sampling and snowball sampling, which at first had a small sample size until the sample size was sufficient for analysis. The sample in this study is an auditor who works in the Surabaya area Public Accountant Firm. The data in this study can be distributed by questionnaires. In this study, the data were analyzed using the Partial Least Square (PLS) approach and using the WarpPLS 6.0 analysis tool. The results of this study state that time budget pressure has a significant effect on audit quality and professional skills can partially mediate time budget pressure on audit quality.